Numerical investigations on the modelling of ultrafine particles in SSH-aerosol-v1.3a: size resolution and redistribution - O. Jacquot; K. Sartelet (Geoscientific Model Development, 2025)
As the health impacts of ultrafine particles become better understood, accurately modelling size distribution and number concentration in chemistry-transport models is becoming increasingly important. The number concentration is strongly affected by processes linked to aerosol dynamics: coagulation, condensation, gas- and particle-phase partitioning, and nucleation. Coagulation is usually solved using an Eulerian approach, relying on a fixed discretization of particle sizes. In contrast, condensation and evaporation processes are rather solved using a Lagrangian approach, requiring redistribution of particles on the fixed-size mesh. Here, a new analytic formulation is presented to compute efficiently coagulation partition coefficients, allowing us to dynamically adjust the discretization of the coagulation operator to the size mesh evolution and therefore solve all the processes linked to aerosol dynamics with a dynamics mesh approach, avoiding the redistribution on the fixed-size grid. This new approach has the advantage of reducing the numerical diffusion introduced by condensation. The significance of these effects on number concentrations is assessed in an idealized box setting, as well as over greater Paris with the chemistry-transport model Polyphemus/Polair3D coupled to the aerosol model SSH-aerosol, using different size resolutions of the particle distribution.